Sleep Hygiene Is the Basis of A Healthy Lifestyle - Turayev Yolqin Sherzod ugli (Academia One Publishing, 2024)
This article contains analytical information about sleep hygiene, which is considered one of the main factors of a healthy lifestyle
Keywords: Healthy body; sleep hygiene; reflex; somatotrope